Analisis Fitokimia Dan Aktivitas Antioksidan Teripang Hitam (Holothuria atra) Dengan Pelarut Berbeda - Muhammad Andika; Lukman Mile; Iin Susilawati Lantu (Universitas Negeri Gorontalo, 2026)
This study aims to analyze the secondary metabolites and antioxidant activity present in black sea cucumber (Holothuria atra) found in Lamu Village. The study stages include sample collection, sampel preparation, and extraction through maceration using methanol (p.a), ethyl acetate (p.a), and N-hexane (p.a) solvents at a 1:20 ratio of material to solvent. The test include phytochemical screening and quantitative methods, applying a Completely Randomized Design (CRD) based on different solvents treatments with three levels: M1 (methanol extract), M2 (ethyl acetate extract), and M3 (N-hexane extract). The data were analyzed using Anlysis of Variance (ANOVA) and the Honestly Significant Difference (HSD) test for significant differences between treatments. The results showed extraction yields of 45% for methanol, 27,5% for ethyl acetate, and 32,5% for N-hexane. Phytochemical tests identified flavonoids and alkaloids in the ethyl acetate extract, and alkaloids and phenols in the N-hexane extract. Antioxidant activity results indicated that the methanol extract exhibited very strong activity (29,18 ppm). In comparison, the ethyl acetate and N-hexane extracts showed strong activity with values of 76,67 ppm and 68,81 ppm, respectively.was 1.871905 ppm. Antibacterial tests showed an inhibition zone of approximately 6 mm, indicating moderate antibacterial activity. These results suggest that ethanol extract of A. marina leaves contains triterpenoid compounds with potential as antibacterial agents. This study opens opportunities for further development of A. marina-derived triterpenoids in antimicrobial formulations.